Pengaruh Corporate Governance dan Sharia Compliance Terhadap Nilai Perusahaan Dalam Penawaran Saham Perdana (Initial Public Offering) Pada Bursa Efek Indonesia - Hidayat, Deni (Sekolah Tinggi Agama Islam Negeri Curup, 2018)
The purpose of this study is to examine the effect of corporate governance and sharia compliance on firm value at the time of initial public offering at Indonesia Stock Exchange. To measure the quality of corporate governance an index is developed based on regulations issued by Financial Service Authority (OJK) and Indonesia Stock Exchange as guidelines. The data used in this study are obtained from prospectus of companies that conducted initial public offering at Indonesia Stock Exchange within period of 2013 to 2016. Using purposive sampling method, 56 companies obtained to be used as research sample and then multiple linear regression is used to test the hypothesis. The result show that there is a positive and significant effect of corporate governance on firm value, indicating that companies with better corporate governance have higher valuation at the time of IPO, while the sharia compliance is not associated with firm value.